2019
DOI: 10.2147/cmar.s209286
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dynamic changes in T-cell subsets and C-reactive protein after radiation therapy in lung cancer patients and correlation with symptomatic radiation pneumonitis treated with steroid therapy</p>

Abstract: ObjectivesTo investigate relationships among serum T-cell subsets, CRP, levels and radiation pneumonitis (RP) in lung cancer patients receiving radiotherapy.MethodsA case–control study with frequency matching was carried out. The case group comprised 36 lung cancer patients who had developed grade ≥2 RP after thoracic radiotherapy. The control group was 36 patients with lung cancer without RP. Patients in the case group received steroid therapy for 1 month after diagnosis of RP and were followed up for 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The tumor of patients with middle or late EC is large, so the postoperative effect is inconsistent due to the difference of their tumor location or tumor size, and prophylactic radiotherapy can further kill the residual tumor, which may be one major reason for the efficacy improvement by prophylactic radiotherapy. We quantified CRP and WBC in the two groups and found after therapy that both groups showed notably increased CRP and WBC, but the levels were not considerably different in both groups, which were in line with results discovered previously [ 19 ]. We reason that for patients with EC, after surgery or postoperative radiotherapy, their body will produce stress response and their CRP and WBC will increase.…”
Section: Discussionsupporting
confidence: 90%
“…The tumor of patients with middle or late EC is large, so the postoperative effect is inconsistent due to the difference of their tumor location or tumor size, and prophylactic radiotherapy can further kill the residual tumor, which may be one major reason for the efficacy improvement by prophylactic radiotherapy. We quantified CRP and WBC in the two groups and found after therapy that both groups showed notably increased CRP and WBC, but the levels were not considerably different in both groups, which were in line with results discovered previously [ 19 ]. We reason that for patients with EC, after surgery or postoperative radiotherapy, their body will produce stress response and their CRP and WBC will increase.…”
Section: Discussionsupporting
confidence: 90%
“…Flt-3 ligand is a known biomarker of hematopoietic injury (Kumar et al, 2018), expression of which was abrogated by GT3. Inflammatory biomarker C-reactive protein (CRP) has also been shown to be an effective indicator of possible radiation pneumonitis in humans (Bai et al, 2019) which was also observed as more than 6 fold increase of the protein in saline treated animals. This increased expression is immediate as of day 1 post-PBI and stayed high even on day 30.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of advanced NSCLC patients treated with chemotherapy, n = 142 patients considered evaluable for cancer related CRP were suggested to have better prognosis if CRP levels decreased after two cycles of treatment [ 16 ], contrary to our findings for the docetaxel arm ( Table 1 ). One confounding factor may be the steroid pretreatment administered with docetaxel that is known to affect CRP levels [ 17 ]. In contrast, in a small study with n = 31 NSCLC patients treated with pembrolizumab monotherapy, the authors found that serum CRP levels at pre-treatment were not predictive, but increase of serum CRP at 6 weeks after anti-PD-1 therapy was predictive of clinical benefit [ 18 ].…”
Section: Discussionmentioning
confidence: 99%